Weather shocks and child nutrition: Evidence from Tanzania - Aimable Nsabimana; Justice Tei Mensah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In this paper, we examine the relationship between childhood exposure to adverse weather shocks and nutritional and health outcomes of children in Tanzania. Using household panel data matched with spatially disaggregated data on weather shocks, we exploit the plausibly exogenous variations in the exposure to weather shocks to estimate the relationship. Our results reveal a positive association between exposure to dry weather shocks and stunting among children. The effects are profound in the first 12 months after childbirth. The findings, however, indicate that wet shocks such as flooding have no discernible impact on child health.
Keywords: I15; Q54; O13; 330; child nutrition; Tanzania; weather shocks